Uso y apropiación del manual de convivencia como estrategia para la resolución de conflictos y la promoción de la convivencia escolar (2018)
Human beings by nature need to relate to others to share, talk, learn, teach, in order to express emotions and needs; this contact with the other is to live together. The educational ineffectiveness of the sanctions used to correct the transgressions is something that stands out in the educational field and the lack of truly applicable strategies that solve the problem, has been generating that this issue becomes a difficult situation for managers, teachers and even for parents. Therefore, the following research seeks to determine the use and appropriation of the manual of coexistence as a strategy for the resolution of conflicts and the promotion of school coexistence in students of the 7th and 7th grades of the educational institution Flower Hill de San Andrés island. We worked through the inductive paradigm to achieve the postulation of laws and principles. The population was formed by 27 seventh grade students. Based on the results it can be concluded that the bodies responsible for the regulation of coexistence of the Flower Hill institution, need a greater active participation in the intermediation of the different cases of coexistence of the institution